1998
DOI: 10.1046/j.1432-1327.1998.2540032.x
|View full text |Cite
|
Sign up to set email alerts
|

The defense‐related rice gene Pir7b encodes an α/β hydrolase fold protein exhibiting esterase activity towards naphthol AS‐esters

Abstract: Acquired resistance of rice to Pyricularia oryzae, the causing agent of rice blast, can be induced by inoculation with the non-host pathogen Pseudomonas syringae pv. syringae. We have previously cloned a cDNA and a corresponding gene (Pir7b) whose transcripts accumulate upon infiltration with the resistance-inducing bacteria. The putative encoded product Pir7b exhibits significant sequence similarity to two recently cloned hydroxynitrile lyases from Manihot esculenta (cassava) and Hevea brasisliensis, enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 4 publications
0
39
0
2
Order By: Relevance
“…In addition, this peptide is similar to several proteins with no proven function, all considered to be part of the large a/b-hydrolase fold proteins (Waspi et al, 1998;Zhong et al, 2001;Marshall et al, 2003). This cDNA was represented only once (0.04%; accession number AW617364) in the LA1777 gland EST database.…”
Section: An Est With Homology To Some Esterases Is Highly Expressed Imentioning
confidence: 88%
See 2 more Smart Citations
“…In addition, this peptide is similar to several proteins with no proven function, all considered to be part of the large a/b-hydrolase fold proteins (Waspi et al, 1998;Zhong et al, 2001;Marshall et al, 2003). This cDNA was represented only once (0.04%; accession number AW617364) in the LA1777 gland EST database.…”
Section: An Est With Homology To Some Esterases Is Highly Expressed Imentioning
confidence: 88%
“…These include, in addition to PNAE and tomato MJE, potato (Solanum tuberosum) MJE (accession number AY684102) and PIR7, a protein from rice (Oryza sativa) that was shown to have esterase activity with artificial substrates (Waspi et al, 1998). In addition, the tobacco (Nicotiana tabacum) SABP2 protein, which has recently been shown to be methyl salicylate esterase (Forouhar et al, 2005), and an uncharacterized protein encoded by an ethyleneinduced citrus EST (Zhong et al, 2001), as well as 20 proteins encoded in the Arabidopsis genome, show similarity to MKS1 (Figure 12).…”
Section: Relationship Of Mks1 To Other A/b-hydrolase Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…New products appeared reproducibly in the syringolin A-treated samples, as shown in the examples of autoradiograms in Figures 4A and 4B. In addition, protein gel blot analysis showed that a wheat homolog of the rice Pir7b esterase, which accumulates in rice plants upon syringolin A treatment (Wäspi et al, 1998b), was induced ( Figure 4C). Thus, syringolin A activates host genes in wheat.…”
Section: Syringolin a Activates Host Genesmentioning
confidence: 76%
“…Proteins were separated on 15% SDS-polyacrylamide gels and blotted onto nitrocellulose membranes using standard methods. Blots were incubated using a 1:1000 dilution of an antiserum obtained by immunizing rabbits with a recombinant Pir7b fusion protein (Wäspi et al, 1998b) in combination with a 1:2000 dilution of a secondary alkaline phosphatase-coupled antirabbit IgG antibody (Boehringer Mannheim). Blots were finally developed in a solution containing 3 mM 4-nitroblue tetrazolium chloride,…”
Section: Protein Extraction and Gel Blot Analysismentioning
confidence: 99%